2006
DOI: 10.1103/physrevlett.96.026102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of an Ising Chain under Local Excitation: A Scanning Tunneling Microscopy Study of Si(100) Dimer Rows at 5 K

Abstract: An extension of the classical Ising model to a situation including a source of spin-flip excitations localized on the scale of individual spins is considered. The scenario is realized by scanning tunneling microscopy of the Si(100) surface at low temperatures. Remarkable details, corresponding to the passage of phasons through the tunnel junction, are detected by the STM within the short span between two atoms comprising an individual Si dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…They demonstrated that the tunneling current recorded above one of the atoms of a dimer of the Ge(001) surface exhibited telegraph like noise. A few years later similar experiments were reported for Si(001) by Hata et al [14], Yoshida et al [15], and Pennec et al [16]. The latter measurements demonstrated that the flip-flop motion of the dimers can be interpreted in terms of a so-called phason.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…They demonstrated that the tunneling current recorded above one of the atoms of a dimer of the Ge(001) surface exhibited telegraph like noise. A few years later similar experiments were reported for Si(001) by Hata et al [14], Yoshida et al [15], and Pennec et al [16]. The latter measurements demonstrated that the flip-flop motion of the dimers can be interpreted in terms of a so-called phason.…”
supporting
confidence: 51%
“…However, it has been well established since than that the lowest energy configuration is a buckled dimer [11,12]. The observed symmetric dimers are actually flip flopping rapidly between the two possible buckled configurations [13][14][15][16]. The first direct evidence for this flip-flop motion was provided by Sato, Iwatsuki, and Tochihara [13].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…They are most likely structural defects or adsorbate-induced ones. Structural defects with a π phase shift in the dimerized chain structure were observed in various systems including the clean Si(001)2×1 [26] and Si(111)5×2-Au surfaces [27].…”
mentioning
confidence: 99%
“…10a is a schematic of such measurement. An STM tip is held just above a target, for example, a Si dimer on a Si(011) surface which rapidly flip-flops between two conformations even at 80K [36,37]. Since the tunneling current depends on the distance between the STM tip and the target material, structural changes can be determined from the corresponding change in the tunneling current.…”
Section: Direct Observation Of Dynamics By Stmmentioning
confidence: 99%